THE EFFECT OF ADAPTIVE LEADERSHIP AND HUMAN RESOURCE DEVELOPMENT ON FACULTY PERFORMANCE, WITH ORGANIZATIONAL CITIZENSHIP BEHAVIOR AS AN INTERVENING VARIABLE (A Study of Tenured Faculty at Muhammadiyah University of Jambi) - Deni Firmansyah; Rahayu Puji Suci (Journal of Education and Teaching Learning, 2026)
The acceleration of internationalization in Indonesian higher education to support the Golden Indonesia Vision 2045 has triggered a phenomenon gap characterized by high administrative workloads that threaten faculty productivity. This study aims to analyze the influence of Adaptive Leadership and Human Resource (HR) Development on Faculty Performance at Universitas Muhammadiyah Jambi (UM Jambi), utilizing Organizational Citizenship Behavior (OCB) as an intervening variable. Employing a quantitative approach, primary data were collected via Likert-scale questionnaires administered to all 73 full-time faculty members through census sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 3.0 alongside Importance-Performance Map Analysis (IPMA). The hypothesis testing results revealed that all direct paths had positive and significant effects (). HR Development showed the strongest direct effect on OCB (), whereas Adaptive Leadership was the primary direct driver of Faculty Performance (). Furthermore, OCB significantly acted as a partial mediator in bridging the impact of both Adaptive Leadership () and HR Development () on Faculty Performance. Theoretically, these findings integrate Adaptive Leadership Theory and Social Exchange Theory, demonstrating that discretionary effort is most effectively triggered when competency investment is paired with flexible leadership. Practically, management is advised to streamline bureaucratic barriers, prioritize capacity-building budgets (doctoral studies and Scopus/WoS publications), and foster a collaborative work culture rooted in Islamic and Muhammadiyah values (AIK).